Penerapan Digital Marketing dan Personal Selling pada Warmienddo.Com: - Chandra, Christy (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2024)
This business report is entitled "Application of Digital Marketing and Personal Selling on Warmienddo.com". The research aims to analyze and evaluate the digital marketing and personal selling strategies implemented by Warmiende.com to improve sales and brand awareness. The research method used is a qualitative method with a case study approach. Data is obtained through in-depth interviews, observations, and documentation. Data analysis is done using descriptive analysis techniques. Research shows that digital marketing, such as using social media, SEO, and email marketing, significantly helps in improving visibility and interaction with customers. On the other hand, personal selling through direct customer communication builds closer relationships and enhances customer satisfaction. This study concludes that combining digital marketing and personal selling can improve Warmienddo.com's overall marketing performance. The recommendations included increased investment in digital platforms and training of sales personnel to maximize the potential of both marketing strategies.